PML‐like subnuclear bodies, containing XRCC1, juxtaposed to DNA replication‐based single‐strand breaks. Issue 2 (27th September 2018) - Kordon, Magdalena M.; Szczurek, Aleksander; Berniak, Krzysztof; Szelest, Oskar; Solarczyk, Kamil; Tworzydło, Magdalena; Wachsmann-Hogiu, Sebastian; Vaahtokari, Anne; Cremer, Christoph; Pederson, Thoru; Dobrucki, Jurek W.
ABSTRACT: DNA lesions induce recruitment and accumulation of various repair factors, resulting in formation of discrete nuclear foci. Using superresolution fluorescence microscopy as well as live cell and quantitative imaging, we demonstrate that X‐ray repair cross‐complementing protein 1 (XRCC1), a key factor in single‐strand break and base excision repair, is recruited into nuclear bodies formed in response to replication‐related single‐strand breaks. Intriguingly, these bodies are assembled immediately in the vicinity of these breaks and never fully colocalize with replication foci. They are structurally organized, containing canonical promyelocytic leukemia (PML) nuclear body protein SP100 concentrated in a peripheral layer, and XRCC1 in the center. They also contain other factors, including PML, poly(ADP‐ribose) polymerase 1 (PARP1), ligase IIIα, and origin recognition complex subunit 5. The breast cancer 1 and ‐2 C terminus domains of XRCC1 are essential for formation of these repair foci. These results reveal that XRCC1‐contaning foci constitute newly recognized PML‐like nuclear bodies that accrete and locally deliver essential factors for repair of single‐strand DNA breaks in replication regions.—Kordon, M. M., Szczurek, A., Berniak, K., Szelest, O., Solarczyk, K., Tworzydlo, M., Wachsmann‐Hogiu, S., Vaahtokari, A., Cremer, C., Pederson, T., Dobrucki, J. W. PML‐like subnuclear bodies, containing XRCC1, juxtaposed to DNA replication‐based single‐strand breaks. FASEB J. 33, 2301–2313 (2019). www.fasebj.org